(untitled) (De Musica, 2021)
This essay is articulated in three sections. In the first one, an analysis of Peter Bürger’s critique of Benjamin’s Kunstwerkschrift allows me to highlight three points, which must in my view be taken into account by any appropriate understanding of the impact of new technologies on our reception of music, and art in general. In the central (and main) section, I will make use of two Benjaminian figures that are symptomatic of the deep social changes in the European metropolis (Paris being a paradigmatic case) during the 19th century, namely the flâneur and the collector, and taking these as hermeneutical tools for understanding, specifically, how the Internet has changed our way of experiencing music. The analyses carried out in Benjamin’s texts lead me to characterize Spotify, one of the main musical platforms of the web, as a hybrid space, where past and future coexist, and where the public space is populated by private collections, thereby constituting a sort of (paradoxical) virtual realization of the Parisian passages, characterized by Benjamin as a space “between the street and the interior”. The final section will provide an overview of the risks and opportunities involved in using Spotify.